2019
DOI: 10.12927/cjnl.2019.25816
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Technology: Enabling Prioritization of Patient Needs and Enhancing the Nurse-Patient Relationship

Abstract: Covering politics, policy, theory and innovations that contribute to leadership in nursing administration, practice, teaching and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…A key finding from this review showed that smartphones and smartphone applications were commonly used technologies in patient care. 26,28,31,32 Indeed, the use of smartphones in healthcare is not unusual, especially that smartphones help healthcare professionals download a wide range of health-related applications that can be readily used in patient care and education. 33 In the present review, nurses' use of smartphones in patient care can be grouped under six broad categories: communicating, 28 directing healthcare information, 26 implementing point of care, 32 securing healthcare information, 32 imparting education, 32 and helping provide quality healthcare to patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A key finding from this review showed that smartphones and smartphone applications were commonly used technologies in patient care. 26,28,31,32 Indeed, the use of smartphones in healthcare is not unusual, especially that smartphones help healthcare professionals download a wide range of health-related applications that can be readily used in patient care and education. 33 In the present review, nurses' use of smartphones in patient care can be grouped under six broad categories: communicating, 28 directing healthcare information, 26 implementing point of care, 32 securing healthcare information, 32 imparting education, 32 and helping provide quality healthcare to patients.…”
Section: Discussionmentioning
confidence: 99%
“…35 Although the use of smartphones in clinical settings was perceived favorably by most participants, some limitations to using such technology among nurses and patients are worthy of note. For instance, nurses in the study by Burkoski et al 28 believed that the poor call quality, interference, system glitches, poor battery life, and stress caused by having multiple notifications were key limitations to using a smartphone in the clinical setting. These challenges are not uncommon and have been reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations